The effects of citrus flavonoids and their metabolites on immune-mediated intestinal barrier disruption using an in vitro co-culture model. Issue 10 (28th November 2022) - Stevens, Yala; de Bie, Tessa; Pinheiro, Iris; Elizalde, Montserrat; Masclee, Ad; Jonkers, Daisy
Abstract: Hesperidin and naringin are citrus flavonoids with known anti-oxidative and anti-inflammatory properties. Evidence from previous studies indicates that both these compounds and the metabolites that are formed during intestinal metabolism are able to exert beneficial effects on intestinal barrier function and inflammation. However, so far, studies investigating the relative contributions of the various compounds are lacking. Therefore, we assessed the effect of citrus flavonoids and their intestinal metabolites on immune-mediated barrier disruption in an in vitro co-culture model. Caco-2 cell monolayers were placed in co-culture with phorbol 12-myristate 13-acetate-stimulated THP-1-Blue™ NF- κ B cells for 30 h. At baseline, the citrus flavonoids and their metabolites were added to the apical compartment (50 or 100 µM per compound). After 24 h, THP-1 cells were incubated with lipopolysaccharide (LPS) in the basolateral compartment for 6 h. Incubation with citrus flavonoids and their metabolites did not induce changes in transepithelial electrical resistance, fluorescein isothiocyanate–dextran 4 kDa permeation or gene expression of barrier-related genes for any of the compounds tested. After LPS stimulation, NF- κ B activity was significantly inhibited by all compounds (100 µM) except for one metabolite (all P ≤ 0·03). LPS-induced production of the cytokines IL-8, TNF- α and IL-6 was inhibited by most compounds (all P < 0·05). However, levels of IL-1 β were increased, which may contribute to the lack of an improved barrier effect. Overall, these results suggest that citrus flavonoids may decrease intestinal inflammation via reduction of NF- κ B activity and that the parent compounds and their metabolites formed during intestinal metabolism are able to exert comparable effects.